Evaluation of storm wave-induced silty seabed instability and geo-hazards: A case study in the Yellow River delta. (June 2016) - Wang, Hu; Liu, Hong-jun
Highlights: Summary and comparison of models for the calculation of wave-induced stresses in a field case study. Systematic evaluation of storm wave-induced silty seabed instability is proposed based on the theoretical framework of soil mechanics. Geo-hazards in the Yellow River delta are described and explained through model calculations. Abstract: Models based on the theoretical framework of soil mechanics are presented to evaluate storm wave-induced silty seabed instability and geo-hazards through a case study in the Yellow River delta. First, the transient and residual mechanisms of wave-induced pore pressure are analyzed. Three typical models (i.e., elastic model, pore pressure development mode and elasto-plastic model) are proposed to calculate wave-induced stresses in the seabed. Next, mechanisms and calculation methods of wave-induced seabed instability modes such as scour, liquefaction, seepage instability and shear slide are proposed. Typical results of storm wave-induced excess pore pressure and seabed instability are given and relevant discussions are made. At last, the formation mechanism of geo-hazards in the Yellow River delta is analyzed based on the proposed mechanism and calculated results. Results and analysis indicate that both transient and residual mechanisms are important to storm wave-induced response of silty seabed and hence the elasto-plastic model is more appropriate. Complete liquefaction does not happen, while other types of instability occur mostly within 2–6 m under the seabed surface. Wave-induced scour, seepage instability and shear slide are all possible instability modes under the 1-year storm waves, and scour is predominant for the 50-year storm waves. The formation mechanism of geo-hazards such as shallow slide and storm wave reactivation, pockmarks, silt flow and gully, disturbed stratum and hard crust in the Yellow River are well explained based on the proposed mechanisms and calculated results of storm wave-induced silty seabed instability.